Textual rivalries : Jesus, midrash, and Kabbalah - Elbom, Gilad, 1968- (Fortress Press, 2022)
In Textual Rivalries Gilad Elbom offers a theology of textuality. By following the prompts provided by medieval kabbalistic exegesis, he argues that the universe is forged of words, God is a linguistic presence, and biblical interpretation is a semiotic practice, one endowed with a self-perpetuating power to repair an imperfect world.